Effect of Supervision and Discipline on Improving Employee Work Effectiveness at Kebayoran Baru Tax Service Office - Harries Madiistriyatno; Sofianto Sofianto (Eduvest - Journal of Universal Studies, 2021)
This research is quantitative, descriptive and associative type. The population in this study is employees. The sampling technique used in this study is simple random sampling. With a simple random sampling technique, a sample of 85 employees was taken at the Tax Service Office in Kebayoran Baru as respondents in this study. The results of this study indicate that: 1) There is an influence of Supervision on the Effectiveness of Employee Work, as evidenced by the tcount for the X1 variable (Supervision) of 3,491, while the value of the table for N = 85 of 1,988. So 3,491> 1,988, it can be concluded that partially the Supervision variable (X1) influences the Employee Work Effectiveness (Y). 2) There is the influence of Discipline on Employee Work Effectiveness, it is proven that the tcount for the X2 variable (Discipline) is 7,222, while the ttable for N = 85 is 1,988. So 7,222> 1,988, it can be concluded that partially the Discipline variable (X2) influences the Employee Work Effectiveness (Y). 3) There is a joint effect of Supervision and Discipline on the Employee Work Effectiveness, as evidenced by the calculated value of 75,695 which is greater than the ftabel value for N = 85 of 2.71 or 75,695> 2.71 with a significant level of 0,000 because 0,000 <0.05, so it can be said that the Supervision variable (X1) and the Discipline variable (X2) jointly relate to the Employee Work Effectiveness variable (Y), with an R Square value of 0.649 meaning that Supervision and Discipline has a 64.9% effect on the Employee Work Effectiveness while the remaining 35.1% is influential with other factors not examined by the authors in this study.